MODELS OF THE LEGAL CONSTRUCT OF CONSENT FOR POST MORTEM ORGAN TRANSPLANTATION ILLUSTRATED BY THE EXAMPLE OF POLAND, NORWAY AND USA - Sarnacka, Emilia (Review of European and Comparative Law, 2017)
Each country which allows for organ transplantation developed legal regula-tions concerning the related procedure the objective of which is to both ensure the safety of the procedure and to prevent trafficking in human organs . There are however substantial differences between the solutions adopted by particular legislators .The most commonly used models include the legal construct of explicit consent (represented by Norwegian legislator) and presumed consent (adopted in Poland) . A half-way model described as a bridge between those two constructs is the gift law construct adopted in the USA .The analysis of particular legal regulations related to transplantology may have an impact on amendments to Polish legislation aiming at an increase in the number of organ transplants .